More Than Just Oligomannose: An N-glycomic Comparison of Penicillium Species - Hykollari, Alba (The American Society for Biochemistry and Molecular Biology, 2016)

(untitled) (Mol Cell Proteomics)
N-glycosylation is an essential set of post-translational modifications of proteins; in the case of filamentous fungi, N-glycans are present on a range of secreted and cell wall proteins. In this study, we have compared the glycans released by peptide/N-glycosidase F from proteolysed cell pellets of three Penicillium species (P. dierckxii, P. nordicum and P. verrucosum that all belong to the Eurotiomycetes). Although the major structures are all within the range Hex(5–11)HexNAc(2) as shown by mass spectrometry, variations in reversed-phase chromatograms and MS/MS fragmentation patterns are indicative of differences in the actual structure. Hydrofluoric acid and mannosidase treatments revealed that the oligomannosidic glycans were not only in part modified with phosphoethanolamine residues and outer chain och1-dependent mannosylation, but that bisecting galactofuranose was present in a species-dependent manner. These data are the first to specifically show the modification of N-glycans in fungi with zwitterionic moieties. Furthermore, our results indicate that mere mass spectrometric screening is insufficient to reveal the subtly complex nature of N-glycosylation even within a single fungal genus.